ROLE OF SURGICAL EXPERIENCE IN REDUCING THE INCIDENCE OF COMMON BILE DUCT INJURY DURING LAPAROSCOPIC CHOLECYSTECTOMY. : JPUMHS;2024:14:03,51-58.http://doi.org/10.46536/jpumhs/2024/14.03.535 - Humaira Yousuf1, Shahnawaz Leghari2, Sajjad Hussain Qureshi3, Maimoona Khushk4, Abdul Rahim Memon5, Ahmed Halepoto6 (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
ABSTRACT BACKGROUND:Common bile duct injury CBDI is a significant complication during laparoscopic cholecystectomy LC, often associated with high morbidity. Previous studies have highlighted the importance of surgical experience in reducing the incidence of CBDI. However, the relationship between surgeon experience and CBDI rates remains to be fully explored. Objective: To evaluate the role of surgical experience in reducing the incidence of CBDI during LC.MATERIALS AND METHODS:This prospective observational study was conducted at Surgical Department within Surgical Units I, II, and III of Peoples Medical College Hospital Nawabshah from 1st March 2024 to 31st August 2024, including 132 patients undergoing elective LC. Patients were classified into three groups based on surgeon experience: Group A 0-20 cases, Group B 21-50 cases, and Group C >50 cases. The incidence of CBDI was recorded, and injuries were classified as minor or major. Data were analyzed in SPSS version 21.0.RESULTS:The overall incidence of CBDI was 8.3%. Group A exhibited the highest rate of CBDI 13.6%, followed by Group B 9.1%, and Group C 2.3%, showing a statistically significant reduction in injury rates with increasing experience p=0.025. Major injuries were only observed in Groups A 4.5% and B 2.3%, while no Long-term outcomes of common bile duct injury: a comparison between open and laparoscopic cholecystectomymajor injuries occurred in Group C p=0.041. Between Groups A and C, there was a statistically significant difference p=0.003, underscoring the protective effect of surgical experience. Conclusion: Surgical experience plays a critical role in reducing the incidence and severity of CBDI during LC. Surgeons with more experience demonstrated a significantly lower rate of complications, reinforcing the importance of expertise and continuous skill development in improving surgical outcomes.